LATAR BELAKANG KECEMASAN ANAK PRA SEKOLAH KASUS A (IM) SISWA TAMAN KANAK-KANAK AR-RAHMAH PALEMBANG - Aslam Tamisa (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2016)
he reseach aims to find out the background of pre-school children's anxiety cases A kindergarten student Ar-Rahmah Palembang. The problem of being discussed is how background anxiety pre-school children. This reseach was a qualitative case study. Data collection techniques using observation, interviews, documentation, and analysis using the concept of